The Impact of Kendari-Toronipa Tourism Access Road on Social Economic and Environmental Conditions (Study in Mekar Village, Bajo Indah Village and Leppe Village, Soropia Sub-District, Konawe Regency) - Sitti Hajrah; Hesty Sukma Dewi (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
The construction of the Kendari-Toronipa tourism access road is one of the significant infrastructure projects in Southeast Sulawesi that is expected to boost the region's economic development. However, infrastructure development in coastal areas often poses significant risks to socio-economic and environmental conditions. This study aims to analyze the impact of the tourism access road on the socio-economic and environmental conditions of the coastal area in Soropia District, Konawe Regency, and formulate a program for improving the welfare of coastal communities based on the current socio-economic and environmental conditions of the coastal area in Soropia District. This research was conducted from January to May 2023. Data were collected through surveys, interviews, and field observations. The main variables analyzed include socio-economic conditions and the coastal environment. Data analysis was conducted using descriptive statistics. Preliminary results show that the construction of the Kendari-Toronipa tourism access road impacts the social, economic, and environmental aspects of Soropia. Improved accessibility, job shifts, and local business growth improve economic welfare. Settlement governance programs, MSME development, and land control maintain the balance of development and environmental sustainability.